Comprehensive Overview of a Process-Oriented Build Tool for Airborne Safety-Critical Software Development - Panchal, Purav; Dmitriev, Konstantin; Myschik, Stephan; Holzapfel, Florian (2023 10th International Conference on Recent Advances in Air and Space Technologies (RAST), 2023)
Rise in software use for safety-critical systems is driven by the escalating technology and curiosity in aerospace and space industries. However, the reliance on software in order to increase features and capabilities of an avionic system is directly questioned by how safe the software is, which further points down to the conformance of the software to standards DO-178C/DO-331. This research presents an overview of a process-oriented build tool developed in MATLAB and Simulink, serving the purpose of increasing the development efficiency along with process conformance. The build tool provides advantages like modular software management, artifacts handling with traceability, tools interlinking, automated model and code verification tasks, defined design environment, etc. It is used in several projects serving as software development environment for as flight control applications as well as battery management systems as well as motor controller. The paper provides motivation and functional overview of the build tool along with its key features.